Matemática, perguntado por gleicykeller10, 1 ano atrás

A=(x+5)ao 2
B=(x-4) ao 2
C=(x-3) ao 2
Determine :
A+b+c
A+b-c

Soluções para a tarefa

Respondido por rosanev
0
A=(x+5)²
B=(x-4)²
C=(x-3)²
Determine :

A+b+c =
(x+5)² + (x-4)² + (x-3)² =
x² + 2x.5 + 25 + x² - 2x.4 + 16 + x² - 2x.3 + 9 =
x² + x² + x² + 10x - 8x - 6x + 25 + 16 + 9 = 3x² - 4x + 50

A+b-c =
(x+5)² + (x-4)² - (x-3)² = 
x² + 2x.5 + 25 + x² - 2x.4 + 16 - (x² - 2x.3 + 9) =
x² + x² - x² + 10x - 8x + 6x + 25 + 16 -9 = x² + 8x + 32

Perguntas interessantes